Determinants of learning effectiveness in SAP-based Enterprise Resource Planning courses - Marfuah, Marfuah; Ditama, Richza Ariyo; Khairunissa, Adinda Khansa (Journal of Contemporary Accounting, 2025)
This study aims to determine the factors that influence learning effectiveness in the SAP-based Enterprise Resource Planning courses at Universitas Islam Indonesia (UII). Based on the Theory of Embodied Learning, this study hypothesizes that activeness, level of suitability, perceived immersion, motivation, and technology support positively affect learning effectiveness in the SAP-based ERP courses. A quantitative method with a survey method was used to collect data from 371 students across six study programs who had taken the SAP-based ERP courses. The results of multiple regression analysis showed that physical involvement, level of suitability, motivation, and technology support had a significant positive effect on the learning effectiveness of SAP-based ERP courses. However, perceived immersion had a significant and negative effect on learning effectiveness in the SAP-based ERP courses, which is contrary to the formulated hypothesis. These findings contribute to ERP curriculum design by emphasizing the importance of active participation, aligning course materials with software features, fostering motivation, and ensuring adequate technology infrastructure to improve learning effectiveness in the SAP-based ERP courses.